Increased intraepithelial CD3+ T-lymphocytes and high PD-L1 expression on tumor cells are associated with a favorable prognosis in esophageal squamous cell carcinoma and allow prognostic immunogenic subgrouping - Jesinghaus, Moritz; Wieczorek, Kathrin (OncoTarget, 2017)
Oncotarget | https://doi.org/10.18632/oncotarget.18606 Moritz Jesinghaus, Katja Steiger, Julia Slotta-Huspenina, Enken Drecoll, Nicole Pfarr, Petra Meyer, Björn Konukiewitz, Marcus Bettstetter, Kathrin Wieczorek,...